2022
DOI: 10.1111/jth.15739
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and determinants of thrombotic and bleeding complications in patients with glioblastoma

Abstract: Background Glioblastoma patients are considered to be at high risk of venous thromboembolism (VTE) and major bleeding (MB), although reliable incidence estimates are lacking. Moreover, the risk of arterial thromboembolism (ATE) in these patients is largely unknown. Our aim was to assess the cumulative incidence, predictors, and prognostic impact of VTE, ATE, and MB on subsequent complications and mortality. Methods Cohort study of 967 consecutive patients diagnosed with glioblastoma between 2004–2020 in two ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 66 publications
(128 reference statements)
0
3
0
1
Order By: Relevance
“…Invasive procedures such as surgery, intravenous access lines and biopsies also carry an increased bleeding risk, notably in anticoagulated patients 2. Finally, the malignant tumour itself may also cause spontaneous bleeding, for example, gastrointestinal, lung or brain tumours 3–5. Hence, even though often clearly indicated, anticoagulant therapy in patients with cancer with VTE or AF is a complicated clinical endeavour, notably during certain periods of the disease, warranting constantly a vigorous balance between bleeding and thrombosis risk.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive procedures such as surgery, intravenous access lines and biopsies also carry an increased bleeding risk, notably in anticoagulated patients 2. Finally, the malignant tumour itself may also cause spontaneous bleeding, for example, gastrointestinal, lung or brain tumours 3–5. Hence, even though often clearly indicated, anticoagulant therapy in patients with cancer with VTE or AF is a complicated clinical endeavour, notably during certain periods of the disease, warranting constantly a vigorous balance between bleeding and thrombosis risk.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be attributed to the shorter exposure time of these patients to the risk of a VTE. Kaptein et al [ 27 ] showed that the median recurrence among GBM was nearly 8 months, varying between 4.8 months and one year. In newly diagnosed HGG patients, Thaler et al [ 61 ] showed that the probability of having a VTE ranged between 3.3 and almost 40% when considering cancer-related factors (e.g., leukocyte and platelet count, P-selectin, prothrombin-fragment 1 + 2, FVIII activity, and D-dimer).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TNFα is thought to be a triggering factor in thrombus formation via activation of the complement system ( Page et al, 2018 ). It might be proposed that increased TNFα in macrophage contributes to the thrombus in glioma ( Czap et al, 2019 ; Kaptein et al, 2022 ). However, the intricate relationship between GPCR, TNF, and coagulation in glioma requires further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%